Interrogation of human microglial phagocytosis by CRISPR genome editing - Chang, Jason Cheng-Yu; Wang, Cheng-You; Lin, Steven (Frontiers in Immunology, 2023)
Microglia are an integral part of central nervous system, but our understanding of microglial biology is limited due to the challenges in obtaining and culturing primary human microglia. HMC3 is an important cell line for studying human microglia because it is readily accessible and straightforward to maintain in standard laboratories. Although HMC3 is widely used for microglial research, a robust genetic method has not been described. Here, we report a CRISPR genome editing platform, by the electroporation of Cas9 ribonucleoproteins and synthetic DNA repair templates, to enable rapid and precise genetic modifications of HMC3. For demonstrations, we targeted the genes implicated in the regulation of amyloid beta (A) and glioblastoma phagocytosis in microglia. Our platform is robust for single (>90%) and double (>70%) knockout (KO) without detectable off-target editing by high throughput DNA sequencing. Co-introduction of DNA repair templates allowed site-specific knock-in (KI) of an epitope tag, a synthetic promoter or a fluorescent reporter gene. We inserted a synthetic SFFV promoter to upregulate the expression of endogenous CD14 and TREM2 genes associated with microglial phagocytosis. The CRISPR-edited HMC3 showed stable phenotypes and enhanced phagocytosis of fluorescence-labeled A1-42 peptides. Confocal microscopy further confirmed the localization of A1-42 aggregates in the acidified lysosomes. HMC3 mutants also changed the phagocytic characteristic toward apoptotic glioblastoma cells. CRISPR genome editing by Cas9 RNP electroporation is a robust approach to genetically modify HMC3 for functional studies such as the interrogation of A and tumor phagocytosis, and is readily adoptable to investigate other aspects of microglial biology.